Evaluasi Implementasi Kebijakan ASN dan Dampaknya terhadap Guru Honorer di Cirebon: Perspektif Engagement dan Trust - Yuna Mumpunu Rahayu; Mahmud Mahmud; Agus Wirabhakti (Simpati, 2026)
This study evaluates the implementation of Indonesia's Civil Service policy on the restructuring of honorary teachers through the Government Employees with Work Agreements scheme and its impact on honorary teachers in Cirebon. The study focuses on two psychosocial factors, namely work engagement and trust, because both factors shape the acceptance of public policies at the school level. A descriptive qualitative case study was conducted in 2025 through open and closed questionnaires and semi-structured interviews involving approximately 150 honorary teachers, civil servant teachers, and school principals from ten junior high schools in Cirebon. The data were analysed using content analysis and simple descriptive statistics. The findings show that trust in the policy and teacher engagement in the implementation process were the most dominant factors. Most respondents perceived the PPPK selection process as insufficiently transparent, while teachers who received information, guidance, and support showed stronger engagement. The study proposes the ASN-Engagement-Trust Framework as a conceptual model for strengthening teacher participation, transparent communication, and fair policy implementation in local education governance.